Discrete pleural masses without effusion in a young man: an unusual presentation of tuberculosis. Issue 5 (May 1989) - Blunt, S B; Harries, M G
Abstract : Extensive tuberculous infection of the pleura presented radiographically as multiple discrete nodules, without associated effusion or lesions of lung parenchyma.